Accentuate of moiré in an interference pattern by defocusing - Ismanov, Yusupzhan Kh.; Tynyshova, Tolgonay D. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
The article considers a mathematical model of an incoherent optical system, into which defocusing is introduced as an aberration. When modeling, it is assumed that if non-coherent lighting is used to illuminate an object, then the transforming optical system should be considered as linear with respect to the intensity of the light. An analysis of the optical system of a general form was carried out, and relations were obtained for a system with a circular pupil, who allowed obtaining defocused images at the output of the optical system, and the defocusing value was rather simply adjustable. The proposed model can be used either as a low-pass filter for preprocessing of interferograms, or as a method for extracting informative image fragments, using which it is possible to synthesize the original image.
Optica Applicata, Vol. 54, 2024, nr 1, s. 105-114
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; incoherent optical system; defocusing; interferogram; frequency spectrum; optical transfer function